Deformation compatibility between nanotwinned and recrystallized grains enhances resistance to interface cracking in cyclic loaded stainless steel. (15th February 2019) - Li, Q.; Yan, F.K.; Tao, N.R.; Ponge, D.; Raabe, D.; Lu, K.
Abstract: Cracks often initiate at phase boundaries in conventional second phase reinforced alloys during cyclic loading, which limits their fatigue properties. Here, we prepared a nanotwin strengthened 316L stainless steel consisting of nanotwinned and recrystallized grains by using plastic deformation and subsequent partial recrystallization annealing. Fatigue tests revealed that interfaces separating hard nanotwinned grains from soft recrystallized ones exhibited excellent resistance to crack initiation. More than half of the cracks (57% in number fraction) are found in recrystallized grains while a small fraction (11%) is observed at the interfaces between nanotwinned and recrystallized grains. This is ascribed to the elastic homogeneity and cyclic deformation compatibility between nanotwinned and recrystallized grains. At small cumulative cyclic strains (below 4000 cycles at σa = 450 MPa), nanotwinned grains deform compatibly with the recrystallized grains without noticeable strain localization at their interfaces. Nanotwins can accommodate cyclic plastic strains by interaction of dislocations with twin boundaries, especially through the motion of the well-ordered threading dislocations inside the twin lamellae. At large cumulative strains, a moderate strain gradient is developed in recrystallized grains surrounding nanotwinned grains as a function of distance from the interfaces due to the occurrence of localized deformation in nanotwinned grains. The nanotwinned grains show high microstructural stability without notable de-twinnning, thus retarding crack initiation and propagation. Therefore, improved fatigue property with high fatigue limit of ∼350 MPa and high fatigue ratio of ∼0.45 is achieved in the nanotwin strengthened stainless steel, which is better than that of conventional second phase reinforced steels with comparable strength. Graphical abstract: Image 1